LINGUISTIC AND CULTURAL CHARACTERISTICS OF METAPHORS IN THE LANGUAGE OF TURKISH SOURCES - Abdujabbarova Feruza Abdunazarovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the article, the linguistic and cultural characteristics of metaphors in the language of Turkish sources are covered based on the work